Horizontes de la narrativa colombiana de las últimas décadas en el ámbito latinoamericano - Carmen Alemany Bay (Caravelle)
The aim of this article is to elaborate a survey of Colombian narrative for the last twenty years of the 20th century. We analyze the main themes beginning with narrative which is based on reality and which diversifies into different genres: urban realism, testimony, detective stories and new historic novels. After the literary space of reality we deal with the supernatural space through an analysis of the most outstanding manifestations of magic realism. The article ends with the study of narrative in Colombian writing.